Safety and target engagement profile of two oxaloacetate doses in Alzheimer's patients. Issue 1 (27th July 2020) - Vidoni, Eric D.; Choi, In‐Young; Lee, Phil; Reed, Gregory; Zhang, Na; Pleen, Joseph; Mahnken, Jonathan D.; Clutton, Jonathan; Becker, Annette; Sherry, Erica; Bothwell, Rebecca; Anderson, Heidi; et al.
Abstract: Introduction: Brain bioenergetics are defective in Alzheimer's disease (AD). Preclinical studies find oxaloacetate (OAA) enhances bioenergetics, but human safety and target engagement data are lacking. Methods: We orally administered 500 or 1000 mg OAA, twice daily for 1 month, to AD participants (n = 15 each group) and monitored safety and tolerability. To assess brain metabolism engagement, we performed fluorodeoxyglucose positron emission tomography (FDG PET) and magnetic resonance spectroscopy before and after the intervention. We also assessed pharmacokinetics and cognitive performance. Results: Both doses were safe and tolerated. Compared to the lower dose, the higher dose benefited FDG PET glucose uptake across multiple brain regions ( P < .05), and the higher dose increased parietal and frontoparietal glutathione ( P < .05). We did not demonstrate consistent blood level changes and cognitive scores did not improve. Conclusions: 1000 mg OAA, taken twice daily for 1 month, is safe in AD patients and engages brain energy metabolism.